The influence of consumption values on green purchase intention: A moderated mediation of greenwash perceptions and green trust - Syed Muhammad Minhal Raza Zaidi; Lai Yifei; Muhammad Yaseen Bhutto; Rizwan Ali; Fahad Alam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Recent years have spotted a majorboost in consumers turning to green consumption due to escalating sustainable development. Following this, how consumption values, green trust and greenwash affect green purchase intention remain unexplored in emerging economy. Drawing on the theory of consumption, this research examines the relationship among consumption values, green trust, andgreen purchase intention. Furthermore, this research also assesses the moderating results of greenwash perception on the relationship between consumption values and green trust in the context of China. Surveys were collected from 207 Chinese organic food consumers at different shopping marts. This research appliesthe structuralequation model (SEM) by using Smart PLS 2.0. The study reveals that functional value (quality and price), and social value have significant effects on green trust. Green trust provesto be a significant mediator between the consumption values and green purchase intention. Moreover, greenwash perceptions have a significant moderating effecton the relationship between consumption values involving functional value quality and epistemic value, and green trust. This study offersa new insight by combining green trust and greenwash perceptions with consumption theory. This study urges firms to place attention on the green trust through paying focus on relevant consumption values, which will help them to leverage the green purchase intention.
Keywords: 330; consumption values; green trust; greenwash perceptions; green purchase intention; sustainable consumption